Social Sustainability of Transit Infrastructure: An Analysis of Factors and Indicators at Jakarta MRT Stations - Endah Aprilia Kriswidyo Pratiwi; Mohammad Arif Rohman (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The rapid development of transit infrastructure in Jakarta has triggered an increase in community mobility; however, the implementation of social sustainability in station projects has not been optimally integrated with technical workflows. Although various project parameters have been proposed, empirical validation of indicators affecting social sustainability using structural equation modeling within the urban railway context remains limited. This study aims to identify and validate key determining indicators of social sustainability in Jakarta Mass Rapid Transit projects. Data were collected through questionnaire surveys administered to active commuters and professional engineering stakeholders, and subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the analysis confirmed a set of valid indicators representing four main variables: community participation, connected construction, project design, and social sustainability. The findings demonstrate that all three independent variables significantly influence social sustainability. Among these variables, the inclusion of public expectations, digital data synchronization, community quality of life, regional connectivity, and fare affordability were identified as the most representative indicators, yielding the highest outer loading values. This study provides an empirical contribution to social infrastructure indicators and offers practical implications for enhancing the quality of transit services.